Thermal preconditioning in a reef-building coral alleviates oxidative damage through a BI-1-mediated antioxidant response - Majerová, Eva; Drury, Crawford (Frontiers in Marine Science, 2022)
Global coral reef decline is largely driven by the breakdown of the coral-algal symbiosis during temperature stress. Corals can acclimatize to higher temperatures, but the cellular processes underlying this ability are poorly understood. We show that preconditioning-based improvements in thermal tolerance in Pocillopora acuta are accompanied by increases in host glutathione reductase (GR) activity and gene expression, which prevents DNA damage. A strong correlation between GR and BI-1 expressions in heat-stressed preconditioned corals and the presence of an antioxidant response element (ARE) in the GR promoter suggest BI-1 could regulate GR expression through Nrf2/ARE pathway. To fortify this link, we developed and GFP-validated an siRNA-mediated gene knockdown protocol and targeted the coral BI-1 gene. BI-1 knock-down specifically decreased GR expression and activity and increased oxidative DNA damage in heat-stressed preconditioned corals, showing that a BI-1-mediated, enhanced antioxidant response during acute heat stress is a key mechanism that prevents oxidative DNA damage after preconditioning.